(untitled) (Scientiae Studia, 2003)
It is useful to work with a model of the practices of scientific research that proposes that there are three key moments at which choices must be made: the moments of (i) adopting a strategy (or methodological rules), (ii) accepting theories, and (iii) applying scientific knowledge. Social values may have legitimate and important roles at the first and third moments, but not the second, where only cognitive values and available empirical data have essential roles. The distinction between cognitive and social values is needed to maintain this model, and thus to sustain the view that impartial scientific knowledge can be the outcome of a process influenced by social values, and to indicate how research must be conducted if the ideal of neutrality is to be upheld more fully. Most of the article is devoted to explaining in detail how the distinction is to be drawn.